A novel dispersive liquid-liquid microextraction using a low density deep eutectic solvent-gas chromatography tandem mass spectrometry for the determination of polycyclic aromatic hydrocarbons in soft drinks - Caldeirão, Lucas; Fernandes, José O.; Gonzalez, Mario Henrique [UNESP]; Godoy, Helena Teixeira; Cunha, Sara C. (Elsevier, 2021)
Ready-to-drink teas can provide, if properly packaged, the taste and wellness character of traditional teas. Nevertheless, in tea processing, there may be several contaminations, among which polycyclic aromatic hydrocarbons (PAHs), anthropogenic contaminants that can present carcinogenic and mutagenic properties. In this work, a novel low-density deep eutectic solvent-based dispersive liquid-liquid microextraction (LDDES-DLLME) procedure followed by gas chromatography tandem mass spectrometry (GC-MS/MS) was optimized for analysis of 15 polycyclic aromatic hydrocarbons (PAHs) in ready-to-drink herbal-based beverages. The new deep eutectic solvent (DES) was synthesized with natural compounds (camphor and hexanoic acid). Several parameters of the extraction procedure such as type and volume of extraction solvent, type, volume of dispersive solvent, and time of extraction were evaluated to achieve the highest yield and to attain the lowest detection limits. The validated method showed very low limits of detection (0.01 μg L−1) and quantification (0.2 μg L−1), good inter- and intra-day precisions (RSD<16.87%), and recoveries higher than 69%. The method was applied to 16 type of samples and it was found total PAHs levels ranging from 0.20 to 1.82 μg L−1. The developed LDDES-DLLME showed a reliable and innovative alternative for the extraction of PAHs from beverages, cost-effective and environmentally friendly, and providing a satisfactory throughput.
Keywords: Environmentally friendly; Food contaminant; Green chemistry; Miniaturized techniques; Tea